2014
DOI: 10.1016/j.sbspro.2014.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Terms of Inclusive Education in Primary Schools – National and School Curriculum

Abstract: In this paper, we bring a summary of the results of qualitative and quantitative analysis of data that are obtained both from the current educational legislation and from curricula samples of Czech primary schools. We focused on the chapters in which these schools declare their options in terms of the teaching of pupils with special educational needs. The result of the comparison is not only to describe the current situation, but also a proposal to optimize the structure and content of these chapters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…Hal ini relevan dengan hasil penelitian Afifa dan Subowo (2020) menunjukkan bahwa pentingnya sekolah membangun kemitraan dengan berbegai lembaga terkait dengan penyelenggaraan pendidikan inklusif untuk bekerjasama dalam pelaksanaan asesmen maupun mitra penyedia sarana dan prasarana. Sekolah mendorong peran aktif orang tua dalam penyelenggaraan pendidikan anaknya (Sudarto, 2016), orang tua membantu dalam proses mendiagnosis ABK, menentukan metode pembelajaran, modifikasi isi materi sesuai dengan kebutuhan ABK (Kratochvílová & Havel, 2014).…”
Section: Pembahasan Faktor Pendukung Penyelenggaraan Pendidikan Inklusifunclassified
“…Hal ini relevan dengan hasil penelitian Afifa dan Subowo (2020) menunjukkan bahwa pentingnya sekolah membangun kemitraan dengan berbegai lembaga terkait dengan penyelenggaraan pendidikan inklusif untuk bekerjasama dalam pelaksanaan asesmen maupun mitra penyedia sarana dan prasarana. Sekolah mendorong peran aktif orang tua dalam penyelenggaraan pendidikan anaknya (Sudarto, 2016), orang tua membantu dalam proses mendiagnosis ABK, menentukan metode pembelajaran, modifikasi isi materi sesuai dengan kebutuhan ABK (Kratochvílová & Havel, 2014).…”
Section: Pembahasan Faktor Pendukung Penyelenggaraan Pendidikan Inklusifunclassified
“…Inclusive education requires institutions of general secondary education to create an enabling environment that allows students to reach their potential and realise themselves, promotes social integration and prepares them for their future employment (Kratochvilova & Havel, 2014).…”
Section: Problem Statementmentioning
confidence: 99%
“…The analysis of the scientific and methodological literature has shown that different sources consider only part of the conditions for the transition to inclusive education, rather than a complete system of conditions. This leads to problems in the practical implementation of the transition to inclusive education (Kratochvilova & Havel, 2014).…”
Section: Problem Statementmentioning
confidence: 99%
“…С подписанием Россией Конвенции ООН о правах инвалидов инклюзивное образование стало инструментом преодоления этой проблемы. Такое образование подразумевает создание чувствительной к потребностям ребенка образовательной среды, которая помогает развить его внутренний потенциал, способствует социальной интегра-ции и будущему трудоустройству [2]. Несмотря на заявленные цели инклюзивного образования, «действительность иногда не позволяет реализовать равное право всех людей в полном мас-штабе в силу многих причин -начиная от общественного мнения, которое выступает как значи-мый барьер в социализации инвалидов и становлении их полноценными членами общества, и заканчивая инфраструктурными проблемами» [3].…”
Section: Inclusive Education In Russia: Providing Implementation Termsunclassified